Enhancing Attendee Engagement: A Study on Designing Successful Hybrid Events in Malaysia - Abd Latif, Nur Hazwani; Zamzuri, Norol Hamiza (Information Management and Business Review, 2024)
This study aims to fill the gap between hybrid events in Malaysia and attendees’ engagement and experience. It is also hoped to provide event stakeholders with information that will help them design successful hybrid events that prioritize attendee engagement and enhance the overall event experience. By understanding the needs and preferences of attendees, event organizers can tailor their strategies to create seamless and interactive experiences for both in-person and virtual participants. This study will contribute valuable insights to the growing field of hybrid events in Malaysia and guide event planners in delivering impactful and memorable experiences to all attendees. From the findings, none of the studies related to hybrid events has been conducted in the Malaysian context. This study was conducted by using electronic database searching from reputable databases such as Scopus, Science Direct and Google Scholar. 52 articles that are related to hybrid events were published from 2014-2023. Hybrid event is a new trend in organizing events. It offers a unique opportunity to cater to both in-person and virtual attendees.